Analisis Pengaruh Lapisan Saprolite pada Timbunan di Atas Tanah Lunak Menggunakan Metode Numerik (PLAXIS 2D) - Yuki Achmad Yakin; Desti Santi Pratiwi; Arinal Ghalibaldi Gazali (Jurnal Serambi Engineering, 2022)
Embankment within soil causes changes in tension within it, which causes deformation to occur and results in stabilization in the soil. The type of soil, method of filling, and degree of density can affect the soil’s technical properties. When embankment work forming a new slope, it is important to analyze the slope’s stability. This study analyzes the effect of elevation, slope, saprolite layer thickness, and depth of replacements using PLAXIS 2D software. The results of the analysis show there are effects from elevation, namely the higher the embankment the greater the decrease and the smaller the safety factor becomes. The slope also has effects and influence, that is the steeper the embankment, the smaller the decrease and the greater the safety factor. Furthermore, there are effects from the replacement’s depth. Namely the thicker the replacement depth results in the decrease in the Short-Term condition becoming larger and the decrease in the Long-Term condition getting smaller.